2017
DOI: 10.1515/bjlp-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Parole Boards’ and Judges’ Decisions on Parole Application in Lithuania

Abstract: This article examines problems of parole application in Lithuania. The research applies a qualitative study in order to learn the peculiarities of the work and decision-making of judges and parole boards. Additionally, this study analyzes social research reports, filled out by staff in correctional facilities. This study covers as many factors influencing parole application as possible, and takes into account the peculiarities of the particular parole stages. Conclusions of this study should help theorists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…These findings are consistent with the results of previous studies regarding parole decision-making (Caplan, 2007;Houser et al, 2019;Huebner and Bynum, 2008;Lindsey and Miller, 2011;Morgan and Smith, 2005;Nuffield, 1982;Proctor, 1999;Warner, 1923). Unlike some previous studies (Heinz et al, 1976;Huebner and Bynum, 2008;Michailovic and Jarutiene, 2017), this study showed that the level of criminal risk appears to be insignificant in terms of parole decision-making. This may indicate that judges tend to focus on the risk factors they believe to be significant in terms of recidivism and public safety.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are consistent with the results of previous studies regarding parole decision-making (Caplan, 2007;Houser et al, 2019;Huebner and Bynum, 2008;Lindsey and Miller, 2011;Morgan and Smith, 2005;Nuffield, 1982;Proctor, 1999;Warner, 1923). Unlike some previous studies (Heinz et al, 1976;Huebner and Bynum, 2008;Michailovic and Jarutiene, 2017), this study showed that the level of criminal risk appears to be insignificant in terms of parole decision-making. This may indicate that judges tend to focus on the risk factors they believe to be significant in terms of recidivism and public safety.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, half of the inmates granted parole were classified as low-risk, while those denied parole were mostly classified as moderate-risk. These findings are consistent previous research indicating judges' beliefs that parolees should mostly be classified as low-risk (Michailovic and Jarutiene, 2017). Although this criterion is included in the CECP, the inmate's progress with risk reduction should also be considered.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations